Studi Deskriptif Mengenai Altruisme pada Mahasiswa Psikologi Universitas âXâ Bandung - Nursanti, Isnaini; Victoriana, Evany; ., Cakrangadinata (Zenit, 2014)
This study aims to get an overview of The Degree of Altruism of psychology students in University “X” Bandung. This study uses descriptive design and stratified sampling technique. Aquestionnaire is made and administered to a total of 325 psychology students. The measuring instrument used in this study is constructed by the researcher, based on Altruism theory by Smith (2011). Validity is measured by using Construct Validity technique with Spearman formula, while reliability is tested by using Split Half technique. Validity calculation discovers 43 valid items with validity coefficient ranging from 0.340 to 0.692. Reliability is measured and it is discovered that the coefficient reliability is 0.957, which means that the measuring instrument is reliable.The data are calculated by using frequency distribution method and it is concluded that a total of 55.4% psychology students has a low degree of altruism, and a total of 44.6% psychology students has a high degree of altruism. Based on its aspects, psychology students whose degree in altruism is low, have a high degree of concern,a high degree of empathy, but a low degree of cost, a low degree of benefit to recipient, and a low degree of ease of escape. Psychology students whose degree in altruism is highalso have a high degree of concern, cost, benefit to recipient, empathy, and ease of escape. For further study, it is suggested conducting a research regarding the correlation betweenaltruism and the factors that influence it, particularly the type of parenting that psychology students experience.Keywords: altruism, psychology students, concern, cost, benefit to recipent, ease of escape.